Learning at work: Researching personal development and competence building in work integration companies - Fernando Marhuenda-Fluixá (Educar, 2017)
The context of our research is Work Integration Enterprises. These hire people who are emerging from processes of social exclusion for a period of between 6 months and three years. In these companies, people work while learning a trade and learning to work, in order to facilitate their entry into the ordinary labour market.